2007
DOI: 10.1080/10428190701377063
|View full text |Cite
|
Sign up to set email alerts
|

The clinical, haematological and morphological profile of patients with myelodysplastic syndromes: A single institution experience from Turkey

Abstract: In a retrospective analysis of 113 patients with primary myelodysplastic syndromes (MDS) diagnosed according to French-American-British (FAB) classification, we evaluated the prognostic impact of FAB and World Health Organisation (WHO) classifications, International Prognostic Scoring System (IPSS), and other clinical and laboratory variables. The median age was 69. IPSS could be applied to 75 patients classified according to the FAB criteria and to 50 patients reclassified according to the WHO criteria. At a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 19 publications
5
9
5
Order By: Relevance
“…The most common presenting complaint in our patients was loss of appetite followed by weakness. In our study mean Hb was 7.7 g/dl which is in concordance with a previous national study [1] and higher as compared to other studies done in Pakistan, China and India [2, 6, 8] and lower as compared to Turkey, Greece and Poland [9, 10, 15]. In our study, mean platelet count was 82 ×10 9 /l, which is in concordance with a national study and also seen in India [1, 8].…”
Section: Discussionsupporting
confidence: 92%
“…The most common presenting complaint in our patients was loss of appetite followed by weakness. In our study mean Hb was 7.7 g/dl which is in concordance with a previous national study [1] and higher as compared to other studies done in Pakistan, China and India [2, 6, 8] and lower as compared to Turkey, Greece and Poland [9, 10, 15]. In our study, mean platelet count was 82 ×10 9 /l, which is in concordance with a national study and also seen in India [1, 8].…”
Section: Discussionsupporting
confidence: 92%
“…Monosomy 7 is not commonly observed in previous studies [3,6,[9][10][11][12][13]15] except for one study from India showing higher frequency [8]. CK in our study was observed to be lower as compared to China [6].…”
Section: Discussioncontrasting
confidence: 45%
“…On the other hand refractory anemia (RA) was most commonly observed in China and Greece [6,10]. In our study, hypoplastic MDS was seen in 23 (13%) which is an interesting finding not observed in previous studies [1][2][3][6][7][8][9][10][11][12][13][14][15]. Refractory cytopenia of childhood (RCC) was observed in only one of our patients.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Our study also supported this opinion. Many previous literatures did not take transfusion requirement as a hazard factor for OS of MDS, but recently many researchers found that transfusion dependency was an independent prognostic factor in MDS patients and can be considered as a reliable indicator of the severity of the disease [6,15,16] . In our study, the prognosis of patients with RBC transfusion dependency was obviously worse than the patients without RBC transfusion requirement.…”
Section: Discussionmentioning
confidence: 99%